2015
DOI: 10.1111/jofo.12085
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use and movement patterns by dependent and independent juvenile Grasshopper Sparrows during the post-fledging period

Abstract: The post-fledging period is a critical life stage for young grassland birds. Habitat selection by recently fledged birds may differ from that of adults and may change as juveniles transition from the care and protection of parents to independence. To describe patterns of habitat selection during these important life stages, we studied habitat use by juvenile Grasshopper Sparrows (Ammodramus savannarum) in a Conservation Reserve Program grassland in Maryland. We used radio-telemetry to track daily movement patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Aggregation could reflect decisions of adult sparrows that prioritize survival and future reproductive potential over the current breeding effort (Hinde et al 2010, Dudeck et al 2018. However, the most isolated territories were only~2 km from aggregation hotspots, distances unlikely to restrict flocking of independent juveniles who move >100 m/d (Small et al 2015). We think this unlikely at this site, however, as sparrow settlement decisions are unrelated to food availability (Williams 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Aggregation could reflect decisions of adult sparrows that prioritize survival and future reproductive potential over the current breeding effort (Hinde et al 2010, Dudeck et al 2018. However, the most isolated territories were only~2 km from aggregation hotspots, distances unlikely to restrict flocking of independent juveniles who move >100 m/d (Small et al 2015). We think this unlikely at this site, however, as sparrow settlement decisions are unrelated to food availability (Williams 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Because of limited battery life for transmitters that can be fit to small songbirds, few researchers have followed fledglings into the independent period. However, those studies that have examined this period have shown that fledglings may use habitat with different vegetative characteristics than those utilized by nesting adults (Vitz and Rodewald 2010, Dittmar et al 2014, Small et al 2015. If this is the case, then management that focuses on providing habitat suited to adults may not meet the needs of fledglings, thereby potentially limiting productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The first phase of dispersal has been well studied for some avian species; however, most studies have focused on small‐scale, post‐fledging movements of species that exhibit short‐duration parental care in only the first year of life (White & Faaborg , Small et al . ). Short‐lived avian species, such as songbirds, spend relatively little time between the onset of independence and successful breeding.…”
mentioning
confidence: 97%
“…Juvenile dispersal is considered to have three distinct phases: (1) departure from parental care, (2) transience, during which individuals investigate the landscape, and (3) settlement, where individuals first defend a breeding territory (Bowler & Benton 2005, Murphy et al 2017). The first phase of dispersal has been well studied for some avian species; however, most studies have focused on small-scale, post-fledging movements of species that exhibit short-duration parental care in only the first year of life (White & Faaborg 2008, Small et al 2015. Short-lived avian species, such as songbirds, spend relatively little time between the onset of independence and successful breeding.…”
mentioning
confidence: 99%